2006
DOI: 10.1007/s00464-005-0086-9
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating the relationship between cardiac preload and renal perfusion under pneumoperitoneum

Abstract: While decreasing preload under extreme lab conditions also decreases RCP, simply creating a pneumoperitoneum of 12 mmHg does not. The decrease in renal blood flow associated with pneumoperitoneum is likely not solely a function of preload.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 37 publications
0
8
0
2
Order By: Relevance
“…The pigs demonstrated great baseline variability, unlike kidney donor patients, who are a fairly homogeneous, healthy population [12]. Although we perform donor nephrectomy clinically at a pneumoperitoneum of 12 mmHg, we chose to use 15 mmHg in this study because we were unable to demonstrate significant changes in systemic and renal hemodynamics at 12 mmHg in a previous porcine study [2]. Nonetheless, Perez et al [31] found a decrease in urine output and creatinine clearance in patients undergoing laparoscopic colon surgery with a pneumoperitoneum of 15 mmHg, despite using crystalloids to maintain the CVP between 10 and 12 mmHg.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The pigs demonstrated great baseline variability, unlike kidney donor patients, who are a fairly homogeneous, healthy population [12]. Although we perform donor nephrectomy clinically at a pneumoperitoneum of 12 mmHg, we chose to use 15 mmHg in this study because we were unable to demonstrate significant changes in systemic and renal hemodynamics at 12 mmHg in a previous porcine study [2]. Nonetheless, Perez et al [31] found a decrease in urine output and creatinine clearance in patients undergoing laparoscopic colon surgery with a pneumoperitoneum of 15 mmHg, despite using crystalloids to maintain the CVP between 10 and 12 mmHg.…”
Section: Discussionmentioning
confidence: 99%
“…This decreases cardiac output, which results in a decrease in effective circulating blood volume and RCP [1,27]. However, we were previously unable to demonstrate a decrease in an index of preload in patients during LLDN at 12-15 mmHg pneumoperitoneum [12] or in a pig model [2,3], and others have even demonstrated an increase in preload during pneumoperitoneum [13,17].…”
mentioning
confidence: 95%
“…In terms of the effects of pneumoperitoneum on cardiac preload and renal perfusion, Bergman et al [8] reported that cardiac preload decreases with pneumoperitoneum and a decrease in preload deepens with concomitant nitroglycerin infusion. Further, renal perfusion is not significantly decreased by pneumoperitoneum alone, but it is decreased when infusion of nitroglycerin is also performed.…”
Section: Discussionmentioning
confidence: 99%
“…The animal model used has been previously described [2]. Briefly, eight female pigs were fasted overnight with free access to water.…”
Section: Animals and Anesthesiamentioning
confidence: 99%